Financialisation and participation in the metropolisation dynamics of European-listed property companies. Issue 2 (9th June 2020) - Coën, Alain; Languillon, Raphaël; Simon, Arnaud; Zaiter, Saadallah
Abstract : Purpose: This paper aims to explore the relationship between the financialisation dynamics of listed property companies (LPCs) and their participation in the metropolisation dynamics, in ten European countries between 2000 and 2017. The study takes place in a context of globalised real estate markets and modification of traditional urban economics. Design/methodology/approach: The measure of financialisation corresponds to a beta increase, in the sense of the capital asset pricing model, and is corroborated by an informativeness index. LPC-owned properties are classified along two spatial segmentations. Panel models are used to analyse the relation between financial and urban hierarchies (through building arbitrages). Findings: Financialisation is generally associated with a decrease in the number of assets owned, especially in the Netherlands and the UK, whereas non-financialised companies tend to increase their number of assets, especially in "flight-to-quality" countries such as Germany and Switzerland. In the first case, non-urban spaces and small and medium urban areas are arbitraged in favour of urban cores and metropoles. In the second, investments are reallocated towards hinterlands and the lower segments of the urban hierarchy. Over the study period, the parallelism between the financial hierarchy and the urban hierarchy was reinforced. Spain illustrates the risks of this evolution, whereas Sweden and Belgium present specificities. Originality/value: This paper illustrates how LPCs function as transmitting channels in the new spatial and urban organisation.